An Analysis of Romania’s Energy Strategy: Perspectives and Developments since 2020 - Alexandru-Mihai BULMEZ; Alin-Ionuț BREZEANU; George DRAGOMIR; Ovidiu-Mircea TALABĂ; Gabriel NĂSTASE (MDPI; Climate, 2024)
Earth’s climate cannot be ignored any longer. Policies are vital in order to mitigate the negative effects of climate change. The energy crisis created by the Russo-Ukrainian war in Europe and COVID-19 pandemic affected the EU and its member states. The focus is more than ever on its energy policies and independence. The EU revised the energy strategy in response to the regional conflict, and it sped up all the processes for energetic independence from other countries outside of the EU. This benefited the climate change policies the most, as all the measures involved reducing energy consumption and increasing renewables, thus contributing to reducing greenhouse gas emissions. As a member state of the EU, Romania is committed to complying with EU regulations. With a high degree of energy independence compared with the other EU members, Romania plans to become a regional energy provider and modernize the energy infrastructure internally as a response to the regional conflict. The measures that the EU and Romania implemented after the conflict started in 2022 have come to fruition, and the effects are becoming visible a year later. This study aims to study the energy strategy of Romania in correlation with the EU strategy in the turbulent period of pandemics and conflict between 2019 and 2023, with the latest available data.